THE ROLE OF INFLAMMATION FACTORS IN THE MECHANISMS OF PROTECTION AND DESTRUCTION OF PERIODONTAL TISSUES - Kim Vitaly Eduardovich; Khabilov Nigman Lukmonovich; Boboev Kodirjon Tukhtaboevich; Gulmukhamedov Pulat Bakhtierovich (Scholar Express Journals, 2023)
The occurrence and course of any disease of an infectious nature is determined by the strength of the body's response [18, 16]. The nature of this response depends on the antigenic specificity of previously acquired immunity and is largely determined by the human genotype [10, 16]. At the same time, only a part of the observed reactions of the body to infection can be considered as protective
Keywords: part; body; reactions; acquired